Consumption of garlic and its interactions with tobacco smoking and alcohol drinking on esophageal cancer in a Chinese population. Issue 4 (July 2019) - Jin, Zi-Yi; Wallar, Gina; Zhou, Jin-Yi; Yang, Jie; Han, Ren-Qiang; Wang, Pei-Hua; Liu, Ai-Min; Gu, Xiao-Ping; Zhang, Xiao-Feng; Wang, Xu-Shan; Su, Ming; Hu, Xu; et al.
Abstract : Garlic consumption has been associated inversely with esophageal cancer (EC); however, its interactions with tobacco smoking and alcohol consumption have never been evaluated in an epidemiological study. We evaluated the potential interactions between garlic intake and tobacco smoking as well as alcohol consumption in a population-based case–control study with 2969 incident EC cases and 8019 healthy controls. Epidemiologic data were collected by face-to-face interviews using a questionnaire. The adjusted odds ratio (OR) and 95% confidence interval (CI) were estimated and additive and multiplicative interactions were evaluated using unconditional logistic regression models, adjusting for potential confounding factors. Semi-Bayes (SB) adjustments were used to reduce potential false-positive findings. EC was associated inversely with raw garlic intake [SB-adjusted OR for more than once a week=0.68, 95% CI: 0.57–0.80], with a strong dose–response pattern in the overall analysis and in the stratified analyses by smoking and drinking. EC was associated positively with smoking and alcohol drinking, with SB-adjusted OR of 1.73 (95% CI: 1.62–1.85) and 1.37 (95% CI: 1.28–1.46) in dose–response effects of increased intensity and longer duration of smoking/drinking. Moreover, garlic intake interacts with smoking [synergy index ( S )=0.83, 95% CI: 0.67–1.02; ratio of OR=0.88, 95% CI: 0.80–0.98] and alcohol drinking ( S =0.73, 95% CI: 0.57–0.93; ratio of OR=0.86, 95% CI: 0.77–0.95) both multiplicatively and additively. Our findings suggested that high intake of raw garlic may reduce EC risk and may interact with tobacco smoking and alcohol consumption, which might shed a light on the development of EC as well as a potential dietary intervention among high-risk smokers and drinkers for EC prevention in the Chinese population.